Patent portfolios and pharmaceuticals: a european perspective - Sílvia Bessa Venda (Market and Competition Law Review)
The book deals with a complex subject, although far from new, which is the intersection between intellectual property (IP) and competition law. Indeed, exclusive rights confer market power and restrict competition temporarily. Along these lines, Emanuela Arezzo, Associate Professor of Commercial Law at the Faculty of Law of the University of Teramo (Italy) and winner of the Jean Monnet Chair in EU Innovation Law & Policy (2023-2026), focuses on the pharmaceutical sector, mostly from the point of view of European Union Law and its Institutions (as opposed, in particular, to the regime of the United States of America). The book highlights recent behaviour trends in this sector, specifically, the building and exploration of patent portfolios.